Correlation of Smoking Habit and Level of Nicotine Dependence in University Students - Dio Alief Supriyanto; Tria Damayanti (Indonesian Society of Respirology (ISR), 2023)
Background: Smoking habits are still a global problem. One of the harmful compounds in cigarettes is nicotine which gives a dependence effect on its users because long-term exposure can cause desensitisation of nicotinic acetyhlcoline receptor. This study aimed to determine the correlation between degree of smoking habit and level of nicotine dependence in actively smoking university students. Method: A cross-sectional study was conducted using questionnaires, consisted of relating factors questionnaire (age, BMI, academic major, allowance, family smoking habits, and social environment), degree of smoking behavior questionnaire (Brinkman Index/IB), and Fagerstorm Test for Nicotine Dependence/FTND questionnaire. Results: There were 124 active smoker university students included in this study. This study found that the higher the BI score, the higher the FTND score (P<0.001; r=0.420). In addition, this study also found that there were positive correlations between age (P=0.009; r=0.223), personal income (P=0.003; r=0.261), and academic major (P=0.042) with the levels of smoking habit. There was also correlation between allowance (P=0.005; r=0.249) with level of nicotine dependence. Conclusion: These results indicate a significant moderate correlation between smoking habit with nicotine dependence among university students.